Identification of multiple eigenmode growth rates towards real time detection in DIII-D and KSTAR tokamak plasmas. (13th April 2021) - Liu, T.; Wang, Z.R.; Boyer, M.D.; Munaretto, S.; Wang, Z.X.; Park, B.-H.; Logan, N.C.; Yang, S.M.; Park, J.-K.
Abstract: The successful application of three-dimensional (3D) magnetohydrodynamic (MHD) spectroscopy enables us to identify the multi-mode eigenvalues in DIII-D and KSTAR tokamak experiments with stable plasmas. The temporal evolution of the multi-modes' stabilities have been detected. The new method is numerically efficient allowing the real time detection of MHD modes' stabilities during the discharge. The method performs active detection of the plasma stability by utilizing the upper and lower rows of internal non-axisymmetric coils to apply a wide variety of 3D fields. Multi-mode eigenvalues are extracted using subspace system identification of the plasma response measured by 3D-field magnetic sensors distributed at different poloidal locations. The equivalence of this new method with the one introduced by Wang (2019 Nucl. Fusion 59 024001) has been numerically corroborated. The more robust and efficient calculation developed here will enable real time monitoring of the plasma stability based on the extracted eigenvalues of stable modes.